Investigating the molecular basis for resistance to the sea louse, Lepeophtheirus salmonis, among salmonids - Braden, Laura Marie (2015)
Co-evolution between parasites and their hosts result in extremely well-orchestrated and intimate relationships that are characterized by remarkable adaptations in the attack response of the parasite and the defense response of the host. To fully understand host-parasite interactions, these adaptations must be considered in the context of the ecological constraints in which they evolved. As a serious pest to salmon mariculture, Lepeophtheirus salmonis has been extensively studied; however, there are still several areas that require further research. Of utmost importance, and the topic of this thesis, is molecular basis for resistance to sea lice. The following chapters investigate this phenomena under the umbrella of ecological immunology using combined modern technologies of transcriptomics, proteomics and functional immunology with a focus on the primary interaction site. In the first chapter, I describe the key players involved in this host-parasite relationship with a focus on the primary interaction site, the louse-salmon interface, where there are responses by the louse (attack) and the salmon host (defense). Previous research indicated that an early aggressive inflammatory response at the louse-skin interface contributes to resistance in coho salmon; however, there are no data characterizing a site-specific response in resistant (pink and coho) and susceptible (Atlantic, chum) species. Accordingly in Chapter 2, I define site-specific cutaneous responses in Atlantic, pink and chum salmon to establish genetic biomarkers of resistance. Chapter 3 focuses on identification of cellular effectors using histochemical localization of biomarkers to characterize cellular populations activated at the louse-attachment site, while broadening the gene targets. Our notion of pink salmon as a resistant species is challenged by the common observation of migrating pink salmon supporting large populations of L. salmonis in the field. Thus the purpose of chapter 4 was to investigate potential mechanisms to explain variations ...